2019
DOI: 10.1111/asej.12167
|View full text |Cite
|
Sign up to set email alerts
|

Workers' Remittances, Capital Inflows, and Economic Growth in Developing Asia and the Pacific

Abstract: This paper examines the impact of remittances on economic growth, using developing countries in Asia and the Pacific as a case study. Using data for the period 1993-2013, our results show that remittances only generate negative and significant impacts on economic growth if they reach 10 percent of GDP or higher. A remittances-to-GDP ratio of below 10 percent could still impact growth negatively, but the effect is statistically insignificant. The present study finds some degree of substitutability between remit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
50
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(57 citation statements)
references
References 31 publications
7
50
0
Order By: Relevance
“…On the effect of remittances on growth, Fayissa and Nsiah (2008) found that remittances promote growth in countries where the level of financial system development is low by providing an alternative source of finance for investment thereby helping the economy overcome liquidity constraints. Jongwanich (2007) in a related study comprising of Developing Asia and Pacific Countries found that remittances have a marginal impact on economic growth but the effect of remittances on poverty reduction was found to be significant. Ncube and Brixiova (2013) also found that remittances impact positively on public debt sustainability in Africa.…”
Section: Empirical Review 221 Remittances and Macroeconomic Variablesmentioning
confidence: 97%
“…On the effect of remittances on growth, Fayissa and Nsiah (2008) found that remittances promote growth in countries where the level of financial system development is low by providing an alternative source of finance for investment thereby helping the economy overcome liquidity constraints. Jongwanich (2007) in a related study comprising of Developing Asia and Pacific Countries found that remittances have a marginal impact on economic growth but the effect of remittances on poverty reduction was found to be significant. Ncube and Brixiova (2013) also found that remittances impact positively on public debt sustainability in Africa.…”
Section: Empirical Review 221 Remittances and Macroeconomic Variablesmentioning
confidence: 97%
“…If remittances are used for investments on human capital, such as healthcare, funding acquisition and education, on the long-term, this A. Adeseye DOI: 10.4236/ojps.2021.111007 101 Open Journal of Political Science will positively have an effect on economic growth. The bond between remittances, economic growth and socio-economic development in emerging countries has become a stimulating topic for researchers (Fagerheim, 2015;Jongwanich, 2017;Sayantan, 2017). Jongwanich (2017) stressed that remittances positively impacted economic growth by helping in reducing of credit boundaries on household income, as they potentially stimulate commercial activity and personal investment.…”
Section: Introductionmentioning
confidence: 99%
“…The bond between remittances, economic growth and socio-economic development in emerging countries has become a stimulating topic for researchers (Fagerheim, 2015;Jongwanich, 2017;Sayantan, 2017). Jongwanich (2017) stressed that remittances positively impacted economic growth by helping in reducing of credit boundaries on household income, as they potentially stimulate commercial activity and personal investment. Fagerheim (2015) and Sayantan (2017) stressed that remittances seem to improve economic growth in countries that adopt an open policy and have better financial institutions and markets to use for productive investments to encourage economic growth.…”
Section: Introductionmentioning
confidence: 99%
“…In developing countries, foreign remittance promotes and stimulates the economic growth, enhances the investment capacity and decreases the liquidity constraints (Giuliano & Ruiz-Arranz, 2009). Foreign remittance helps developing countries reduce poverty level (Jongwanich, 2007) and contributes to socio-economic development (Barai, 2012;Rao & Hassan, 2012). In case of monetary benefits, foreign remittance has a great contribution to a country's educational development, increasing health facilities and gender equality which ultimately leads to the human development of a country.…”
Section: Introductionmentioning
confidence: 99%